An expanded cohort study of cancer among benzene-exposed workers in China. Benzene Study Group. - Yin, S N (1996)
An expanded cohort study of 74,828 benzene-exposed and 35,805 unexposed workers were followed during 1972 to 1987, based on a previous study in 12 cities in China. A small increase was observed in total cancer mortality among benzene-exposed compared with unexposed workers (relative risk [RR] = 1.2). Statistically significant excesses were noted for leukemia (RR = 2.3), malignant lymphoma (RR = 4.5), and lung cancer (RR = 1.4). When risks were evaluated by leukemia subtype, only acute myelogenous leukemia was significantly elevated (RR = 3.1), although nonsignificant excesses were also noted for chronic myelogenous leukemia (RR = 2.6) and acute lymphocytic leukemia (RR = 2.3). A significant excess was also found for aplastic anemia.